Laterality effects on performance in team sports : Insights from soccer and basketball - Stöckel, T.; Carey, D. P. (Laterality in Sports: Theories and Applications, 2016)
This chapter reviews some of the literature on laterality effects in team sports with a focus on soccer and basketball. First, footedness/handedness distributions among soccer/basketball players from different competitive levels were analyzed to explore whether the bias in foot/hand preference is reduced in these athletes as compared to the general population. Second, we tried to establish if any of the sport-specific behaviors are more or less lateralized than any others. Third, we reviewed the influence of soccer- and basketball-specific training on the proficiency and use of both feet/hands to examine whether or not increasing amounts of bilateral practice can change skill and choice of both sides. Last, potential implications for practitioners in team sports as well as for future research are inferred from the literature reviewed in this chapter.